2017
DOI: 10.1371/journal.pone.0189108
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance in solvent-exposed vehicle collision repair workers in New Zealand

Abstract: ObjectivesTo assess whether contemporary solvent exposures in the vehicle collision repair industry are associated with objectively measured neuropsychological performance in collision repair workers.MethodsThe RBANS battery and additional tests were administered to 47 vehicle collision repair and 51 comparison workers randomly selected from a previous questionnaire study.ResultsCollision repair workers performed lower on tests of attention (digit span backwards: -1.5, 95% CI -2.4, -0.5; digit span total: -1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(70 reference statements)
0
3
1
Order By: Relevance
“…Another research that is in line with this research is the study on workshop workers in New Zealand. The results of this study found that there was no relationship between age and neurotoxic complaints (Keer et al, 2017).…”
Section: Correlation Between Age and Health Complaintscontrasting
confidence: 50%
“…Another research that is in line with this research is the study on workshop workers in New Zealand. The results of this study found that there was no relationship between age and neurotoxic complaints (Keer et al, 2017).…”
Section: Correlation Between Age and Health Complaintscontrasting
confidence: 50%
“…The effect of work duration was assessed by dividing collision repair workers into tertiles which were then ‘rounded’ to the nearest decade of work duration, i.e. those who had worked in the industry <10 years, (average of 4.0 years; range 0.2–9.9), 10–20 years (average 14.3 years (10.1–19.9)), and >20 years (average 30.8 years (20.0–57.0)), as described previously [ 20 , 21 ]. Construction workers were also stratified according to their specific trade, based on company profiles and questionnaire responses i.e.…”
Section: Methodsmentioning
confidence: 99%
“…more than 5 packs in whole life and not a current smoker or; current smoker, i.e. more than 5 packs in whole life and still smoke [ 20 , 24 ]) were also included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation